Evaluating the Role of Life Events and Sustaining Conditions in Weight Loss Maintenance - Eleni Epiphaniou; Jane Ogden (Journal of Obesity)
Background. Recent qualitative research indicates that life events can enhance behaviour change maintenance. if a number of sustaining conditions are met. This study aimed to quantitatively test this theory in the context of weight loss maintenance. Method. Based upon their weight histories participants were classified as either successful (𝑛=431) or unsuccessful (𝑛=592) dieters and all completed questionnaires relating to life events, choice, the function of eating and exercise and the model of their weight problem. Findings. Successful dieters reported a higher number of life events than unsuccessful dieters particularly for events such as “clothes did not fit me”, “doctor's recommendation” and “reached my heaviest weight”. Successful participants also indicated reduced choice over their previous unhealthy diet, more choice over their exercise behaviours and more benefits from the new healthy behaviours. They were also less likely to attribute their previous increased weight to any medical and psychological factors. This was accompanied by a belief about the effectiveness of behavioural solutions to their weight problem. Discussion. Life events can promote behaviour change for some individuals. This change is facilitated by a reduction in choice and disruption of function over the unhealthy behaviours, and a belief that behavioural solutions will be effective.